Pemahaman Konsep Dan Motivasi Belajar Matematika Siswa Kelas X Madrasah Aliyah Negeri 1 Palu Melalui Model Pembelajaran Berbasis Masalah Dan Model Pembelajaran Inkuiri - Eva Setya Rini (Mitra Sains, 2016)
This study aimed to describe the influence of learning model and learning motivation through conceptual understanding students. This research was conducted at Madrasah Aliyah Negeri 1 Palu using a quasy-experimental design with factorial 2 × 2. The independent variable is a learning model and learning motivation. Learning model are problem based learning model and inquiry learning model. Learning motivation investigated that were high learning motivation and low learning motivation. Dependent variable is conceptual understanding students. There was using two instruments, there were (1) a questionnaire of learning motivation that used before learning activity and (2) a test of conceptual understanding students was used after learning activity. These samples included s 48 students at grades X students, who were chosen by random sampling. Analysis of data using analysis of variance two-lane. The result of this research was shown that was difference conceptual understanding and learning motivation of tenth grade students of madrasah aliyah negeri 1 palu through problem-based learning model and inquiry learning model.